Chronic Rhinosinusitis with Nasal Polyps: Targeting IgE with Anti-IgE Omalizumab Therapy - Kariyawasam HH; James LK (Dove Medical Press, 2020)
Harsha H Kariyawasam,1– 3 Louisa K James4 1Specialist Allergy and Clinical Immunology, Royal National ENT Hospital, University College London Hospitals NHS Foundation Trust, London, UK; 2Department of Rhinology, Royal National ENT Hospital, University College London Hospitals NHS Foundation Trust, London, UK; 3University College London, London, UK; 4Blizard Institute, Barts and the London School of Medicine and Dentistry, Queen Mary University of London, London, UKCorrespondence: Harsha H KariyawasamSpecialist Allergy and Clinical Immunology, Royal National ENT Hospital, University College London Hospitals NHS Foundation Trust, 47-49 Huntley Street, London WC1E 6DG, UKEmail harsha.kariyawasam@nhs.netAbstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a complex, clinically heterogeneous and persistent inflammatory disorder of the upper airway. Detailed mechanistic insights into disease pathogenesis are lacking, but it is now accepted that local tissue IgE driven T2-high inflammatory pathways are critical to disease. The recent CRSwNP Phase 3 POLYP1 and POLYP2 replicate studies of blocking IgE with omalizumab confirmed rapid improvements in all clinical parameters of sinonasal disease, confirming a pivotal role for IgE driven inflammatory pathways in CRSwNP. This review summarises the biology of IgE in relation to CRSwNP. Insight into how IgE may drive CRSwNP is evaluated in the context of clinical improvements seen with omalizumab. The need for further studies using a broader patient and biomarker specific groups to aid more precise drug-patient selection alongside more detailed mechanistic studies of omalizumab in CRSwNP is highlighted.Keywords: IgE, nasal polyps, omalizumab, rhinosinusitis